A Wearable Nutrition Tracker. Issue 1 (23rd November 2020) - Zhao, Jiangqi; Nyein, Hnin Yin Yin; Hou, Lei; Lin, Yuanjing; Bariya, Mallika; Ahn, Christine Heera; Ji, Wenbo; Fan, Zhiyong; Javey, Ali
Abstract: Nutrients are essential for the healthy development and proper maintenance of body functions in humans. For adequate nourishment, it is important to keep track of nutrients level in the body, apart from consuming sufficient nutrition that is in line with dietary guidelines. Sweat, which contains rich chemical information, is an attractive biofluid for routine non‐invasive assessment of nutrient levels. Herein, a wearable sensor that can selectively measure vitamin C concentration in biofluids, including sweat, urine, and blood is developed. Detection through an electrochemical sensor modified with Au nanostructures, LiClO4 ‐doped conductive polymer, and an enzymes‐immobilized membrane is utilized to achieve wide detection linearity, high selectivity, and long‐term stability. The sensor allows monitoring of temporal changes in vitamin C levels. The effect of vitamin C intake on the sweat and urine profile is explored by monitoring concentration changes upon consuming different amounts of vitamin C. A longitudinal study of sweat's and urine's vitamin C correlation with blood is performed on two individuals. The results suggest that sweat and urine analysis can be a promising method to routinely monitor nutrition through the sweat sensor and that this sensor can facilitate applications such as nutritional screening and dietary intervention. Abstract : A wearable nutrient tracker that allows monitoring of vitamin C in sweat, along with urine and blood, to assist tracking users' nutritional status is demonstrated. A longitudinal study is performed on two individuals to explore correlations of vitamin C concentrations in sweat and urine with blood. It has promising potential applications in nutritional assessment and dietary intervention.